Adsorbent for desulfurization process as well as preparation method and application of adsorbent

By preparing a desulfurization process adsorbent with high porosity and high carbon adsorption, using carbon materials, modified asphalt and dry sludge, the influence of carbon-containing particles in blast furnace gas on the desulfurization process is solved, the use cycle of protective agents and catalytic hydrolyzers is extended, the cost is reduced and the reaction efficiency is improved.

CN119633755APending Publication Date: 2025-03-18CHINALCO ENVIRONMENTAL PROTECTION & ENERGY CONSERVATION GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510095835.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

After the carbon-containing particulate matter in the blast furnace gas enters the protective agent layer, it will compete with HCl for the adsorption site and block the protective agent channel, resulting in the inability to completely remove HCl, affecting the desulfurization efficiency. The use period of the protective agent and catalytic hydrolyzer is relatively short and needs to be replaced frequently, which increases the cost of the drug.

Method used

A desulfurization process adsorbent is adopted, and the preparation method includes mixing carbon materials, modified asphalt and dry sludge and pressing them into molding, and then sintering to obtain an adsorbent with high porosity and high carbon adsorption properties. The adsorbent can effectively adsorb carbon-containing particles in blast furnace gas, extending the use cycle of protective agents and catalytic hydrolyzers.

Benefits of technology

By using the desulfurization process adsorbent, the use cycle of the protective agent and the catalytic hydrolyzer is significantly improved, the process operation cycle is extended for more than 18 days, the agent cost is reduced, and the reaction efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633755A_ABST
    Figure CN119633755A_ABST
Patent Text Reader

Abstract

The invention relates to the field of gas desulfurization, in particular to a desulfurization process adsorbent as well as a preparation method and application thereof. The present invention provides a desulfurization process adsorbent preparation method, which comprises: mixing a carbon material, modified pitch and dried sludge, and carrying out compression molding to obtain an adsorbent green body; and sintering the adsorbent green body to obtain the desulfurization process adsorbent. The preparation method provided by the invention is simple, the raw materials are easy to obtain, and the obtained desulfurization process adsorbent can effectively adsorb carbon-containing particles in blast furnace gas and remarkably prolong the operation cycle of the process, so that the service cycles of a protective agent and a catalytic hydrolysis agent are prolonged, and the cost of the blast furnace gas desulfurization process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coal gas desulfurization, and in particular to a desulfurization process adsorbent and a preparation method and application thereof. Background Art

[0002] Blast furnace gas is a by-product of the blast furnace ironmaking production process. It contains high calorific value components such as carbon monoxide and hydrogen, and is an important secondary energy source. In addition to combustible components, blast furnace gas also contains a small amount of sulfide (mainly carbonyl sulfide), which will generate sulfur dioxide during the combustion process as fuel at the back end, increasing the cost of terminal flue gas treatment. Therefore, blast furnace gas is centrally desulfurized before use to reduce the cost of terminal flue gas treatment. In addition to sulfides, blast furnace gas is also accompanied by chlorides, carbon-containing particulate matter, etc. Therefore, the flue gas is usually preliminarily dusted before desulfurization, and then dry fine desulfurization is carried out.

[0003] In the alkaline dry desulfurization process, the front-end protective agent bed is usually used to adsorb acidic gases such as HCl to avoid the poisoning effect of acidic gases on the catalytic hydrolyzer. The deacidified gas then enters the catalytic hydrolysis unit to remove organic sulfur (carbonyl sulfide, carbon disulfide, etc., accounting for about 80% of the total sulfides), and finally H2S is removed in the terminal adsorption unit.

[0004] However, after the carbonaceous particles in the blast furnace gas enter the protective agent layer, they will compete with HCl for adsorption sites and block the protective agent pores. The lack of protective agent pores and reduced porosity will reduce the chlorine capacity (reduced effective adsorption capacity) and the rate of HCl adsorption (reaction rate is lower than the escape rate), resulting in HCl not being completely removed. After HCl enters the catalytic hydrolysis unit, it has a negative effect on the base catalytic hydrolyzer, which further affects the catalytic hydrolysis of organic sulfur, ultimately leading to a decrease in desulfurization efficiency. In order to meet sulfur dioxide emission standards, it is necessary to frequently replace protective agents and catalytic hydrolyzers, and the cost of the agents is relatively high. Therefore, how to extend the service life of protective agents and catalytic hydrolyzers is a problem that needs to be solved urgently in this field. Summary of the invention

[0005] The invention provides a desulfurization process adsorbent and a preparation method and use thereof. The adsorbent has a simple preparation process and readily available raw materials, can effectively adsorb carbonaceous particles in blast furnace gas, and significantly improves the service life of a protective agent and a catalytic hydrolyzing agent.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a desulfurization process adsorbent, comprising the following steps:

[0007] The carbon material, modified asphalt and dried sludge are mixed and pressed into a shape to obtain an adsorbent green body.

[0008] The adsorbent green body is sintered to obtain the desulfurization process adsorbent.

[0009] Optionally, the carbon material includes at least one of metallurgical coke, activated carbon and petroleum coke, and the particle size of the carbon material is ≤150 μm.

[0010] Optionally, the ratio of the mass of volatile solids to the total mass of solids in the dried sludge is 0.4-0.7, and the particle size of the dried sludge is ≤150 μm.

[0011] Optionally, the mass ratio of the carbon material, modified asphalt and dried sludge is 1:0.25-0.5:0.1-0.2.

[0012] Optionally, the mixing is performed at 150-180°C.

[0013] Optionally, the sintering is performed in an atmosphere of protective gas, the sintering temperature is 500-1000° C., the sintering time is 50-70 min, and the heating rate to the sintering temperature is 14-17° C. / min.

[0014] The present invention also provides a desulfurization process adsorbent obtained by the preparation method described in the above technical solution.

[0015] Optionally, the porosity of the desulfurization process adsorbent is 57-64%

[0016] The present invention also provides the use of the desulfurization process adsorbent described in the above technical solution in the blast furnace gas fine desulfurization process.

[0017] Optionally, the desulfurization process adsorbent is arranged at the front end of the protective agent bed layer of the blast furnace gas fine desulfurization process.

[0018] The present invention provides a method for preparing a desulfurization process adsorbent, comprising the following steps: mixing a carbon material, modified asphalt and dried sludge, pressing and molding to obtain an adsorbent green body, sintering the adsorbent green body, and obtaining a desulfurization process adsorbent. The present invention uses a carbon material as a matrix, modified asphalt as a binder, and dried sludge as a pore-forming agent to prepare an adsorbent green body, and then sintering the adsorbent green body, pyrolyzing the organic matter in the dried sludge, completing pore formation, and obtaining an adsorbent with high porosity and high carbon adsorption. The desulfurization process adsorbent obtained by the preparation method of the present invention has a high porosity. The desulfurization process adsorbent can effectively remove carbonaceous particles in blast furnace gas, and extend the process operation cycle by more than 18 days, thereby effectively extending the use cycle of the protective agent and the catalytic hydrolyzing agent in the blast furnace gas fine desulfurization process, thereby improving the reaction efficiency.

[0019] In addition, the desulfurization process adsorbent of the present invention has a simple preparation process, the raw materials are easily available, and waste sludge is used as the raw material, which has the advantages of low cost and resource utilization. The desulfurization process adsorbent of the present invention has a high carbon content and can be used as fuel after adsorbing carbonaceous particles in the blast furnace gas fine desulfurization process without secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and other objects, features and advantages of the present invention will be apparent from the following description of preferred embodiments and accompanying drawings which illustrate the subject matter of the present invention and its use, in which:

[0021] Figure 1 These are the initial porosity test results of the protective agent, catalytic hydrolyzing agent, and the desulfurization process adsorbent obtained in Examples 1-6.

[0022] Figure 2 It is the porosity loss rate of the protective agent before and after using the desulfurization process adsorbent obtained in Examples 1-6.

[0023] Figure 3 It is the porosity loss rate of the catalytic hydrolyzer before and after using the desulfurization process adsorbent obtained in Examples 1-6.

[0024] Figure 4 The process operation cycle test results when the desulfurization process adsorbent obtained in Examples 1-6 is used.

[0025] Figure 5 It is the porosity loss rate and process operation cycle after using the desulfurization process adsorbent obtained in Comparative Example 1-2. DETAILED DESCRIPTION

[0026] The present invention will be described below by specific embodiments, and it will be appreciated by those skilled in the art that the following specific embodiments are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following embodiments, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following embodiments, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be adopted to process.

[0027] The present invention provides a method for preparing a desulfurization process adsorbent, comprising the following steps:

[0028] The carbon material, modified asphalt and dried sludge are mixed and pressed into a shape to obtain an adsorbent green body.

[0029] The adsorbent green body is sintered to obtain the desulfurization process adsorbent.

[0030] The present invention uses carbon material as a matrix, modified asphalt as a binder and dried sludge as a pore-forming agent to prepare a desulfurization process adsorbent. Among them, carbon materials are widely available, easy to obtain, and have low cost. After the reaction is completed, they can also be burned as fuel, and have strong resource recovery properties. Modified asphalt is composed of hydrocarbon elements. During the subsequent heat treatment, it will volatilize and separate from the surface, leaving sufficient pore structure, and the modified asphalt has a high coking value, carbon content and viscosity. During the heat treatment, a large amount of porous structure is left, which is conducive to the adsorption of poisoning factors (carbonaceous particles and condensed tar). The dried sludge is used as a pore-forming agent. During the sintering step, pores are formed, and after the sintering is completed, the remaining part is biochar. There are multiple functional groups on the biochar, which can enhance the adsorption performance. The biochar has a high calorific value and can be mixed with coal to reduce carbon dioxide emissions. The desulfurization process adsorbent prepared by the joint action of carbon materials, modified asphalt and dried sludge has excellent adsorption performance for carbonaceous particles, and can be set at the front end of the blast furnace gas fine desulfurization process to pretreat the blast furnace gas to protect the protective agent and the catalytic hydrolyzer and extend the service life of the protective agent and the catalytic hydrolyzer.

[0031] In some embodiments of the present invention, the carbon material includes at least one of metallurgical coke, activated carbon and petroleum coke, and the particle size of the carbon material is ≤150 μm. In the present invention, the carbon material of the above particle size is conducive to uniform dispersion. In some embodiments of the present invention, when the particle size of the carbon material is large, the carbon material can be crushed or ground, and then sieved to obtain a carbon material of the desired particle size. In some embodiments of the present invention, after the carbon material is ground, it is passed through a 100-200 mesh sieve, and the sieve is taken as a raw material to be mixed with modified asphalt and dried sludge.

[0032] The present invention has no special limitation on the modified asphalt, and conventional modified asphalt that meets the YB / T5194-93 standard can be used. In an embodiment of the present invention, the modified asphalt is modified coal tar, which meets the standard of YB / T5194-93 first-class product. In the present invention, the modified asphalt is used as a binder, and its softening point is relatively low (generally 100-110°C), and it can be mixed at a relatively low temperature. In addition, during the sintering process, the volatilization separates from the surface, leaving a pore structure, which is beneficial to improving the adsorption performance.

[0033] In some embodiments of the present invention, the ratio of the mass of volatile solids to the total mass of solids in the dried sludge is 0.4-0.7, and can specifically be 0.4, 0.5, 0.6, 0.7 and any value between the values. In some embodiments of the present invention, the dried sludge is dried sludge from a sewage plant, that is, the residual sludge of the sewage plant is obtained by drying, and the ratio of the mass of volatile solids to the total mass of solids in the dried sludge corresponds to the ratio of the volatile suspended solids concentration of the mixed liquor of the residual sludge to the suspended solids concentration of the mixed liquor (abbreviated as MLVSS / MLSS ratio). Therefore, the ratio of the mass of volatile solids to the total mass of solids in the dried sludge can also be abbreviated as MLVSS / MLSS ratio. The dried sludge in the above-mentioned MLVSS / MLSS ratio range is conducive to obtaining a desulfurization process adsorbent with better adsorption performance. In some embodiments of the present invention, the particle size of the dried sludge is ≤150μm, and can specifically be ≤106μm or ≤75μm. The dried sludge of the above-mentioned particle size can ensure that the dried sludge is more easily mixed with other raw materials. In some embodiments of the present invention, when the particle size of the dried sludge is large, the dried sludge can be crushed or ground, and then sieved to obtain the dried sludge of the desired particle size. In some embodiments of the present invention, after the dried sludge is ground, it is passed through a 100-200 mesh sieve, and the sieve is taken as a raw material to be mixed with the carbon material and modified asphalt. The present invention uses dried sludge as a pore-forming agent, which has the advantages of a wide source, high organic content and low cost compared to other pore-forming agents.

[0034] In some embodiments of the present invention, the mass ratio of the carbon material, modified asphalt and dried sludge is 1:0.25-0.5:0.1-0.2; specifically, the mass ratio of the carbon material and modified asphalt is 1:0.25-0.5, and can be 1:025, 1:0.35, 1:0.5 and any value between the above ratios; the mass ratio of the carbon material to dried sludge is 1:0.1-0.2, and can be 1:0.1, 1:0.15, 1:0.2 and any value between the above ratios; the mass ratio of the carbon material, modified asphalt and dried sludge can satisfy the above-mentioned mass ratio of the carbon material and modified asphalt and the mass ratio of the carbon material to dried sludge.

[0035] In some embodiments of the present invention, the mixing is carried out at 150-180°C, specifically 150°C, 165°C, 180°C and any value between the above values. In the present invention, the mixing temperature affects the viscosity of the modified asphalt. If the temperature is too high, false stickiness is likely to occur. If the temperature is too low, the viscosity of the material is large, the fluidity decreases, and it cannot be mixed evenly. The present invention does not have any special restrictions on the mixing time, as long as the materials can be mixed evenly. The present invention does not have any special restrictions on the mixing time, as long as the materials can be mixed evenly. In an embodiment of the present invention, the mixing time is 20-40 minutes, preferably 30 minutes.

[0036] The present invention does not specifically limit the specific method of the compression molding and the shape of the obtained green body, and those skilled in the art can select according to needs, such as extrusion and pelletization. In the embodiment of the present invention, a spherical adsorbent green body is obtained by compression molding. In some embodiments of the present invention, the compression molding pressure is 10MPa.

[0037] In some embodiments of the present invention, the sintering is carried out in an atmosphere of protective gas, and the protective gas is nitrogen or an inert gas (such as argon). In the present invention, the protective gas atmosphere can avoid excessive consumption of carbon in the adsorbent green body and ensure that a suitable pore structure is obtained. In some embodiments of the present invention, the sintering temperature is 500-1000°C, and can be specifically 500°C, 750°C, 1000°C and any value between the above values. In some embodiments of the present invention, the sintering time is 50-70min, and can be specifically 50min, 60min, 70min and any value between the above values. In some embodiments of the present invention, the heating rate of heating to the sintering temperature is 14-17°C / min, and can be specifically 14°C / min, 15°C / min, 16°C / min, 17°C / min and any value between the above values. In the present invention, the above heating rate can ensure uniform heating and moderate energy consumption; the desulfurization process adsorbent obtained at the above sintering temperature and time has a higher porosity and better adsorption performance.

[0038] In some embodiments of the present invention, after sintering, the obtained desulfurization process adsorbent is naturally cooled to room temperature.

[0039] The present invention also provides a desulfurization process adsorbent obtained by the preparation method described in the above technical solution.

[0040] In some embodiments of the present invention, the porosity of the desulfurization process adsorbent is 57-64%, specifically 57.3%, 58.1%, 59.6%, 60.4%, 62.7%, 63.4% and any value therebetween.

[0041] The present invention also provides the use of the desulfurization process adsorbent described in the above technical solution in the blast furnace gas fine desulfurization process.

[0042] In some embodiments of the present invention, the desulfurization process adsorbent is arranged in front of the protective agent bed of the blast furnace gas fine desulfurization process. In the present invention, the desulfurization process adsorbent is arranged in front of the protective agent bed of the blast furnace gas fine desulfurization process to pre-treat the blast furnace gas, and the carbonaceous particles therein can be removed to protect the protective agent and the catalytic hydrolyzing agent.

[0043] In an embodiment of the present invention, the blast furnace gas fine desulfurization process comprises the following steps:

[0044] The blast furnace gas is sequentially passed through an adsorbent bed, a protective agent bed, a catalytic hydrolysis unit and an adsorption unit to obtain desulfurized gas; wherein the adsorbent bed is filled with the desulfurization process adsorbent described in the aforementioned technical solution.

[0045] The present invention does not specifically limit the process conditions of the adsorbent bed, and those skilled in the art can adjust them according to specific circumstances. In the embodiment of the present invention, the air velocity of the adsorbent bed is 10000h -1 , the temperature is 130℃.

[0046] The present invention has no special restrictions on the protective agent used in the protective agent bed, the catalytic hydrolyzing agent used in the catalytic hydrolysis unit, the reagent used in the terminal adsorption unit, and the process conditions of each unit. Conventional protective agents, catalytic hydrolyzing agents, and process conditions can be used. In the embodiment of the present invention, the protective agent used in the protective agent bed is a dechlorinating agent, and the air velocity is 1000h -1 , the temperature is 130℃; the catalytic hydrolyzing agent of the catalyst hydrolysis unit is carbonyl sulfide hydrolyzing agent, and the space velocity is 1000h -1 , the temperature is 110℃; the terminal adsorption unit is filled with iron-based desulfurization agent, and the air velocity is 500h -1 , the temperature is 50℃.

[0047] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. The embodiments of the present application are only used as examples, and all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] The metallurgical coke and the dried sludge (MLVSS / MLSS ratio is 0.7) are ground respectively and passed through a 100-mesh sieve to obtain granular metallurgical coke and granular dried sludge;

[0050] The granular metallurgical coke, modified asphalt and granular dried sludge were blended at 150° C. for 30 minutes in a mass ratio of 1:0.25:0.1 to obtain a blend;

[0051] The blend was pressed into small balls with a particle size of 5±0.5 mm at a pressure of 10 MPa to obtain an adsorbent green body;

[0052] The adsorbent green body was heated to 500°C at a rate of 15°C / min under a nitrogen atmosphere, sintered at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a desulfurization process adsorbent.

[0053] Example 2

[0054] The metallurgical coke and the dried sludge (MLVSS / MLSS ratio is 0.5) are ground respectively and passed through a 150-mesh sieve to obtain granular metallurgical coke and granular dried sludge;

[0055] The granular metallurgical coke, modified asphalt and granular dried sludge were blended at 165° C. for 30 min in a mass ratio of 1:0.35:0.15 to obtain a blend;

[0056] The blend was pressed into small balls with a particle size of 5±0.5 mm at a pressure of 10 MPa to obtain an adsorbent green body;

[0057] The adsorbent green body was heated to 750°C at a rate of 15°C / min under a nitrogen atmosphere, sintered at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a desulfurization process adsorbent.

[0058] Example 3

[0059] The metallurgical coke and the dried sludge (MLVSS / MLSS ratio is 0.4) are ground respectively and passed through a 200-mesh sieve to obtain granular metallurgical coke and granular dried sludge;

[0060] The granular metallurgical coke, modified asphalt and granular dried sludge were blended at 180° C. for 30 min in a mass ratio of 1:0.5:0.2 to obtain a blend;

[0061] The blend was pressed into small balls with a particle size of 5±0.5 mm at a pressure of 10 MPa to obtain an adsorbent green body;

[0062] The adsorbent green body was heated to 1000°C at a rate of 15°C / min under a nitrogen atmosphere, sintered at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a desulfurization process adsorbent.

[0063] Example 4

[0064] The activated carbon and dried sludge (MLVSS / MLSS ratio is 0.5) were ground separately and passed through a 100-mesh sieve to obtain granular activated carbon and granular dried sludge;

[0065] The granular activated carbon, modified asphalt and granular dried sludge were blended at a mass ratio of 1:0.25:0.15 at 180° C. for 30 minutes to obtain a blend;

[0066] The blend was pressed into small balls with a particle size of 5±0.5 mm at a pressure of 10 MPa to obtain an adsorbent green body;

[0067] The adsorbent green body was heated to 1000°C at a rate of 15°C / min under a nitrogen atmosphere, sintered at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a desulfurization process adsorbent.

[0068] Example 5

[0069] The activated carbon and dried sludge (MLVSS / MLSS ratio is 0.7) were ground separately and passed through a 150-mesh sieve to obtain granular activated carbon and granular dried sludge;

[0070] The granular activated carbon, modified asphalt and granular dried sludge were blended at 150° C. for 30 minutes in a mass ratio of 1:0.35:0.1 to obtain a blend;

[0071] The blend was pressed into small balls with a particle size of 5±0.5 mm at a pressure of 10 MPa to obtain an adsorbent green body;

[0072] The adsorbent green body was heated to 750°C at a rate of 15°C / min under a nitrogen atmosphere, sintered at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a desulfurization process adsorbent.

[0073] Example 6

[0074] The activated carbon and the dried sludge (MLVSS / MLSS ratio is 0.4) are ground separately and passed through a 200-mesh sieve to obtain granular metallurgical coke and granular dried sludge;

[0075] The granular metallurgical coke, modified asphalt and granular dried sludge were blended at 165° C. for 30 minutes in a mass ratio of 1:0.5:0.2 to obtain a blend;

[0076] The blend was pressed into small balls with a particle size of 5±0.5 mm at a pressure of 10 MPa to obtain an adsorbent green body;

[0077] The adsorbent green body was heated to 500°C at a rate of 15°C / min under a nitrogen atmosphere, sintered at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a desulfurization process adsorbent.

[0078] The desulfurization process adsorbent obtained in Examples 1-6 has a regular shape without powdery debris, which indicates that the desulfurization process adsorbent obtained in the present invention has good strength.

[0079] Performance Test:

[0080] 1. Porosity test

[0081] The porosity in this application is tested by the following method: dry the sample at 60°C for 24 hours, measure the dry weight, and then soak the sample in water for 24 hours. After soaking, wipe the surface moisture and measure the wet weight. The porosity is calculated according to the following formula:

[0082]

[0083] 2. Porosity loss determination

[0084] This application uses the following formula to test porosity loss to characterize the porosity change after a process operation cycle.

[0085]

[0086] 3. Determination process

[0087] This application uses the following process to test the process operation cycle of adsorbent, protective agent, and catalytic hydrolyzing agent:

[0088] The blast furnace gas is passed through the adsorbent bed, protective agent bed, catalytic hydrolyzer bed and terminal adsorption unit in sequence, wherein the adsorbent bed is filled with desulfurization process adsorbent, and the air velocity is 10000h -1 , the temperature is 130℃; the protective agent used in the protective agent bed is a dechlorinating agent, and the air velocity is 1000h -1 , the temperature is 130℃; the catalytic hydrolyzing agent of the catalyst hydrolysis unit is carbonyl sulfide hydrolyzing agent, and the space velocity is 1000h -1 , the temperature is 110℃; the terminal adsorption unit is filled with iron-based desulfurization agent, and the air velocity is 500h -1 , the temperature is 50℃.

[0089] At the end of a process operation cycle, the sulfur content in the final exhaust gas exceeds 20 mg / Nm 3 shall prevail.

[0090] The initial porosity of the protective agent, catalytic hydrolyzing agent and the desulfurization process adsorbent obtained in Examples 1-6 was measured. The results are as follows: Figure 1 shown.

[0091] Use the above method to test the pore loss rate of the protective agent and the catalytic hydrolyzer after a process operation cycle, and record the time of a process operation cycle; use the above method to remove the adsorbent bed filled with the desulfurization process adsorbent, and test the pore loss rate of the protective agent and the catalytic hydrolyzer at the end of a process operation cycle when the desulfurization process adsorbent is not used, and record the time of the process operation cycle. The test results are as follows: Figure 2-4 shown.

[0092] Depend on Figure 2 and 3 It can be seen that after using the desulfurization process adsorbent of the present invention, at the end of a process operation cycle, the porosity loss rate of the protective agent and the catalytic hydrolyzing agent is significantly reduced, indicating that the desulfurization process adsorbent provided by the present invention effectively removes carbon-containing particles in blast furnace gas, improves the porosity retention rate of the protective agent and the catalytic hydrolyzing agent, thereby extending the service life of the protective agent and the catalytic hydrolyzing agent.

[0093] Depend on Figure 4 It can be seen that compared with the desulfurization process without using desulfurization process adsorbent ( Figure 4 As for the "original system" in the text, after pre-treating blast furnace gas with the desulfurization process adsorbent obtained by the present invention, the process operation cycle can be extended by more than 18 days. It can be seen that the process operation cycle is significantly extended, thereby effectively extending the service life of the protective agent and the catalytic hydrolyzing agent, and significantly reducing the cost of the blast furnace gas desulfurization process.

[0094] In addition, the desulfurization process adsorbent obtained in Examples 1-6 has a high carbon content and can be used as fuel after the reaction is completed.

[0095] Comparative Example 1

[0096] The desulfurization process adsorbent was prepared by the method of Example 1, except that an equal amount of clay was used instead of modified asphalt.

[0097] Comparative Example 2

[0098] The desulfurization process adsorbent was prepared by the method of Example 1, except that an equal amount of ammonium carbonate was used as the pore-forming agent instead of dried sludge.

[0099] The above method was used to test the process operation cycle when the desulfurization process adsorbent obtained in Comparative Example 1-2 was used, as well as the porosity loss rate of the desulfurization process adsorbent, protective agent and catalytic hydrolyzing agent after one process operation cycle. The results are as follows Figure 5 As shown. Figure 5It can be seen that the process operation cycle of the desulfurization process adsorbent obtained in Comparative Example 1 is longer to a certain extent (190 days) compared with not using the desulfurization process adsorbent, but it is still 8 days shorter than that in Example 1, and after one operation cycle, the porosity loss rates of the protective agent and the catalytic hydrolyzing agent are higher than those of the process using the desulfurization process adsorbent obtained in Examples 1-6; the process operation cycle (195 days) when using the desulfurization process adsorbent obtained in Comparative Example 2 is equivalent to the process operation cycle when using the desulfurization process adsorbent obtained in Example 1, but the price per ton of ammonium carbonate is much higher than that of dried sludge, and it does not have a cost advantage.

[0100] While preferred embodiments of the present invention have been shown and described, it is contemplated that those skilled in the art may devise various modifications of the present invention within the spirit and scope of the appended claims.

Claims

1. A method for preparing a desulfurization process adsorbent, comprising the following steps: The carbon material, modified asphalt and dried sludge are mixed and pressed to obtain an adsorbent green body, and the adsorbent green body is sintered to obtain a desulfurization process adsorbent.

2. The preparation method according to claim 1, characterized in that: The carbon material comprises at least one of metallurgical coke, activated carbon and petroleum coke, and the particle size of the carbon material is ≤150 μm.

3. The preparation method according to claim 1, characterized in that: The ratio of the mass of volatile solids to the total mass of solids in the dried sludge is 0.4-0.7, and the particle size of the dried sludge is ≤150 μm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the carbon material, modified asphalt and dried sludge is 1:0.25-0.5:0.1-0.

2.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The mixing is carried out at 150-180°C.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The sintering is carried out in an atmosphere of protective gas, the sintering temperature is 500-1000° C., the sintering time is 50-70 min, and the heating rate to the sintering temperature is 14-17° C. / min.

7. A desulfurization process adsorbent obtained by the preparation method according to any one of claims 1 to 6.

8. The desulfurization process adsorbent according to claim 7, characterized in that: The porosity of the desulfurization process adsorbent is 57-64%.

9. Use of the desulfurization process adsorbent according to claim 7 or 8 in a blast furnace gas fine desulfurization process.

10. The use according to claim 9, characterized in that The desulfurization process adsorbent is arranged at the front end of the protective agent bed layer of the blast furnace gas fine desulfurization process.